Relationship between social support and loneliness levels among hypertensive elderly individuals - Haidar Al Fatih; Erna Erawati; Angga Sugiarto; Sunarko (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Elderly people are a vulnerable age group who are susceptible to various health issues, including hypertension, which can affect their quality of life. In contrast, social support plays a significant role in improving the psychological well-being of the elderly population. This study aims to examine the relationship between social support and feelings of loneliness in elderly individuals suffering from hypertension. Purposes: This research aims to examine the relationship between social support and the level of loneliness in the elderly suffering from hypertension. Methods: A quantitative approach with a cross-sectional design was employed in this study, involving elderly respondents as participants. A total of 53 respondents were selected using total sampling. The instruments used are the UCLA Loneliness Scale ver-3 and the Multidimensional Scale of Perceived Social Support (MSPSS). Result: From this research, 75% of the respondents are female, 83% are aged 60-74 years, and 47% live with a partner. A significant association between social support and the level of loneliness was found with a p-value of 0.023. Conclusion: In conclusion, this study demonstrates a relationship between social support and loneliness levels in the elderly population.We recommend that social support should be contribute to the development of more effective intervention programs to support the well-being among the elderly with hypertension.